ANALISIS JUMLAH KEBUTUHAN PEGAWAI BERDASARKAN PENGUKURAN BEBAN KERJA PADA RUPBASAN KELAS II WATES - Muryanti, Dwi; Assery, Syeh (Jurnal Riset Manajemen Akuntansi Indonesia, 2024)
Civil servants (PNS) are required to work professionally. However, in reality, the expected professionalism has not been fully realized. The main reason is that there is a mismatch between the competence of the employee and their position. Likewise, the distribution of civil servants at this time still does not refer to the actual needs of the organization, it means that it is not based on the existing workload. The accumulation of employees is other units without a clear job and the deficiency of employees in other units is a clear example of this problem. This study aims to determine the condition of the workload, the number of employee needs based on the results of the workload analysis and the efforts that the organization can do to optimize the Human Resources in Rupbasan Kelas II Wates. This research used descriptive qualitative method. Based on the study of documents and the results of the analysis of research data, it shows that the workload conditions in the Rupbasan Kelas II Wates are very high (overload capacity) and the number of employee needs currently 9 (nine) employees. Some efforts to optimize existing human resources by training, utilizing the information and technology, providing supporting facilities, providing employee rewards, performance evaluation and comparative studies (benchmarks).